Implementasi Sistem Pakar Deteksi Dini Resiko Penyakit Jantung Koroner Menggunakan Metode Backward Chaining dan Certainty Factor pada Android - Andreas Prasetyo; Rudy Adipranata; Indar Sugiarto (Jurnal Infra, 2021)
Lifestyle in the modern era today can have a harmful impact on ourlives, one of which is coronary heart disease. Coronary heartdisease is the chronic and acute heart's inability to pumpoxygenated blood due to a lack of blood supply in the heart's musclecells.This research, using the backward chaining method, serves to tracethe facts and combine them with hypotheses that can strengthenthose facts. Certainty factor is the method used to measure thecertainty of the facts that have been made and provide results in theform of scoring to determine the level of accuracy of the facts thathave been given by experts.This research will produce an expert-system application that isuseful for early detection of coronary heart disease. Output will bein the form of grouped results, which is the results of a person'spotential risk of coronary heart disease, along with a percentagebased risk potential of developing said disease. It is hoped that thecreation of this system will make it easier for a person to detect thedisease based on daily habits, so it can later be used as the initialdiagnosis whether or not a person has said disease.